The Influence of Burnout and Job Stress Through Job Satisfaction on Employee Engagement at PT. Kiki Ratu Intan Express Jambi - Vincent Nathaniel Thalib; Arna Suryani; Sudirman Sudirman (Green Publisher, 2026)
This research is motivated by the declining number of employees at PT. Kiki Ratu Intan Express Jambi, which indicates low employee engagement, allegedly caused by burnout, job stress, and job satisfaction. The research gap in this study lies in the inconsistency of previous findings regarding the effect of burnout on job satisfaction, as well as the mediating role of job satisfaction in the relationship between burnout and job stress on employee engagement. This study aims to examine the effect of burnout and job stress on employee engagement, with job satisfaction as a mediating variable. The research method employs a quantitative approach with a saturated sample of 70 employees. Data analysis was conducted using SmartPLS. The results show that job stress and burnout significantly affect employee engagement, while job satisfaction mediates the effect of job stress on employee engagement but does not mediate the effect of burnout. The novelty of this research lies in the finding that burnout affects employee engagement directly without passing through job satisfaction, in contrast to job stress, whose effect is mediated by job satisfaction. The research model explains 79.4% of the variance in employee engagement. This study recommends stress management and burnout prevention as strategies to improve employee engagement.